Internet sexual solicitation of children: a proposed typology of offenders based on their chats, e-mails, and social network posts. Issue 1 (2nd January 2017) - DeHart, Dana; Dwyer, Gregg; Seto, Michael C.; Moran, Robert; Letourneau, Elizabeth; Schwarz-Watts, Donna
ABSTRACT: Although researchers have examined sexual solicitation of minors online, there is limited research on the content and patterns of victim-offender chats. These chats have potential use in investigations for triaging and prioritising cases, enhancing understanding of offenders, developing treatments, and crafting education and policy to prevent sexual solicitation of minors online. As part of a broader effort on Internet crimes against children (ICAC), we examine offender chat logs, email threads, and social network posts from state and local task forces on ICAC for a sample of 200 offenders in communications with undercover officers. We use mixed-methods analyses to identify key elements in these cases and propose a typology of online solicitation offenders: cybersex-only offenders, schedulers, cybersex/schedulers, and buyers. These findings provide support and expansion of existing research on offender types using a larger and more geographically diverse sample. Implications for research, practice, and policy are discussed.